(untitled) (International journal of artificial intelligence, 2025)
The art of satire occupies a special place in the spiritual culture of humanity. It reveals various shortcomings in society, social injustices, and situations that are both amusing and thought-provoking. In world experience, the forms of satire in theater, literature, cinema, and television have great significance in social development. This article examines the historical and chronological stages of humorous programs on Uzbek television and their significance.